2013
DOI: 10.1136/jmedgenet-2013-101670
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the 5′exons ofCOL4A6is not needed for the development of diffuse leiomyomatosis in patients with Alport syndrome

Abstract: These observations suggest that deletion of the 5' exons of COL4A6 and of the common promoter of the COL4A5 and COL4A6 genes is not essential for the development of leiomyomatosis in patients with ATS, and that COL4A5_COL4A6 deletions extending into COL4A6 exon 3 may not result in ATS-DL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Twenty-two (37%) of the 60 probands had a pathogenic mutation in COL4A5, of which 12 (57%) were novel and 9 (43%) had been previously described (Table 1) (5,9,(12)(13)(14)(15)(16)(17). Eighty percent of the probands who presented with all four diagnostic criteria, but only 1 of 3 of those who presented with two or three criteria, had a pathogenic mutation in COL4A5.…”
Section: Methodsmentioning
confidence: 98%
“…Twenty-two (37%) of the 60 probands had a pathogenic mutation in COL4A5, of which 12 (57%) were novel and 9 (43%) had been previously described (Table 1) (5,9,(12)(13)(14)(15)(16)(17). Eighty percent of the probands who presented with all four diagnostic criteria, but only 1 of 3 of those who presented with two or three criteria, had a pathogenic mutation in COL4A5.…”
Section: Methodsmentioning
confidence: 98%
“…Mutations in this gene are associated with the X-linked Alport syndrome, also known as hereditary nephritis (16,17,20,21). Deletions of the 5'-ends of both COL4A5 and COL4A6, including the intergenic region, were found in Alport syndrome associated with diffuse leiomyomatosis (22)(23)(24)(25)(26). Furthermore, whole-genome sequencing analysis showed that a subset of uterine leiomyomas harbored somatic deletions within the COL4A5-COL4A6 locus (27).…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse esophageal leiomyomatosis associated with X-linked Alport syndrome has been well described and may imply a contiguous gene deletion involving the 5′exons of COL4A5 and COL4A6 genes [2–4] . Diffuse leiomyomatosis is characterized by circumferential thickening of smooth muscle layers of the esophagus and should be distinguish from leiomyoma which are well circumscribed benign tumor, usually single and rarely multiple [5] .…”
Section: Discussionmentioning
confidence: 99%